1999
DOI: 10.1007/s100529900097
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbative renormalization of lattice four-fermion operators without power subtractions

Abstract: A general non-perturbative analysis of the renormalization properties of ∆I = 3/2 four-fermion operators in the framework of lattice regularization with Wilson fermions is presented. We discuss the non-perturbative determination of the operator renormalization constants in the lattice Regularization Independent (RI or MOM) scheme. We also discuss the determination of the finite lattice subtraction coefficients from Ward Identities. We prove that, at large external virtualities, the determination of the lattice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…We found that these effects are even below the 0.3% level and thus fully under control. The N f =3 configurations are used to compute the required renormalization constants nonperturbatively using the RI-MOM method [7,8].…”
Section: Lattice Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that these effects are even below the 0.3% level and thus fully under control. The N f =3 configurations are used to compute the required renormalization constants nonperturbatively using the RI-MOM method [7,8].…”
Section: Lattice Detailsmentioning
confidence: 99%
“…We denote their bare matrix elements K 0 |O i |K 0 by Q i . The renormalization pattern is then given by [8] Q ren…”
Section: Nonperturbative Renormalizationmentioning
confidence: 99%
“…These operators can be written as three color-unmixed (quarks in a bilinear are contracted together) and two color-mixed (quarks in different bilinears are contracted together) operators. The mixing patern is determined by the chiral properties of these operators [8,11,12]. The operator basis is given by:…”
Section: Short Range Contributionsmentioning
confidence: 99%
“…Hence, we expect any mixing with wrong chiralities to be predominantly of infrared origin, due to the spontaneous breaking of chiral symmetry via quark condensates, and to vanish at high momenta. Based on CPS symmetry arguments [39][40][41], we also expect the parity odd projectors to show less contaminations compared to the parity even case.…”
Section: Non-perturbative Effectsmentioning
confidence: 99%